Catalytic Activity of Single-Atom Copper Modified Reconstructed Cerium Dioxide (100) Surface for Ammonia Oxidation: A DFT+U Study (Communications in Computational Chemistry, 2025)
Ammonia has been proposed as a potential carbon-free energy source. However, a highly active catalystis required for ammonia oxidation to promote the combustion rate. In this study, the single-atomcopper catalyst loaded on the reconstructed cerium dioxide (100) surface with the pocket-like structure($Cu_1$/$CeO_4$-t-p) is constructed for ammonia oxidation, and the catalytic process is investigated usingthe density functional theory calculations corrected by on-site Coulomb interactions (DFT+U). Theadsorptions of ammonia and oxygen, the dissociation of ammonia and the oxidation of the dissociatedammonia species are systematically examined.